ВИЗНАЧЕННЯ ПРОФІЛЮ СОЛЕНОЇДА ДЛЯ СТВОРЕННЯ ІМПУЛЬСНОГО МАГНІТНОГО ПОЛЯ НА ПЛОСКІЙ ГРАНИЦІ ПРОВІДНИКА - Михайлов, В.М.; Петренко, М.П. (Інститут електродинаміки Національної академії наук України, 2018)
Method of magnetic flux continuation using system of coaxial annular elementary conductors with currents and corresponding Green’s function applied to flat boundary surface is developed. Green’s functions for axisymmetric magnetic field of system of annular elementary conductor – perfectly superconducting half-space are received. Samples of determination of massive single-turn solenoids, which generating given magnetic induction distribution on flat surface of conductor with sharp skin effect are given. Conformity check of received profiles to given boundary field distributions is implemented. Influence of profile top part cut on magnetic induction distribution is investigated.   References 9, figures 4, table.